Plant Growth-Promoting Microbe Mediated Uptake of Essential Nutrients (Fe, P, K) for Crop Stress Management: Microbe–Soil–Plant Continuum - Pattnaik, Swati; Mohapatra, Balaram; Gupta, Abhishek (Frontiers in Agronomy, 2021)
The indiscriminate and intensive use of agrochemicals in the developing nations to enhance the crop productivity has posed an alarming threat to soil quality, fertility, biodiversity, food safety, agricultural sustainability, and groundwater quality, thus critically affecting the planetary health and food productivity. Additionally, both abiotic and biotic stresses and developmental disorders i.e. disease susceptibility, hormonal imbalance, and nutritional deficiency are the major constraints on crop productivity. In this context, the use of soil-plant associated microbiomes “phytomicrobiome” especially rhizospheric microbiota, in combination with agronomic practices (nutrient-, water-, and resource-management, as integrated management options: INM/IPM/IWM) is most promising alternative for managing soil health and crop productivity. The global recognition of plant/soil associated microbiome has generated substantial investment of public and private bodies to grow microbe-based food products. However, understanding the molecular, genetic, physiology and ecological aspects of phytomicrobiome towards sustainable agriculture would require broad attention along with associated environmental/physico-chemical control points. The underpinning mechanisms of plant-microbe interactions are of immense significance for strategizing host-selection (single culture/consortia) and its field application. Taxa like Rhizobium, Pseudomonas, Alcaligenes, Burkholderia, Sphingomonas, Stenotrophomonas, Arthrobacter, Bacillus, Rhodococcus have been emerged as promising plant growth promoting (PGP) candidates with diverse beneficial traits like producing phyto-hormones, volatile organics, antibiotics for disease suppression, N2-fixation, Fe-uptake, extracellular enzymes, etc. But, several physico-chemical constraints/extremities limit field application (on-site) of such microbes. Hence, a detailed overview on genomic, physiological, metabolic, cellular, and ecological aspects is necessitated. thorough insights into the nutrient acquisition (especially limiting nutrients like Fe, P, K) during abiotic stress are still under-studied. So, use OMICS, robust bioinformatics pipeline/tools might greatly revolutionize the field of PGP microbial ecology (complex plant-microbe interactions) for application in agricultural sustainability, nutritional security and food safety. This review focusses on critical aspects of mechanisms of Fe and P transport-uptake (nutrient acquisition) by various PGP microbes, their metabolism, genetics and physiology, relevant for managing stress and better crop production